Going "green" from gray: Providing opportunities of community development and sustainability within a correctional facilities program. Issue 3 (2nd July 2020) - Hoffman, August John
Abstract: This quasi-experimental study examined the community and psychosocial benefits in the development of a "green space" environmental project (apple fruit tree orchard) among community residents and inmates in a minimum security prison in St. Paul, MN. Seventeen ( n  = 17) participants volunteered in the development of an apple tree orchard located on the grounds of a prison facility located in Ramsey County, MN. Participants (inmates and community residents) prepared the planting area (two acres) and planted a variety of 60 fruit bearing apple trees (Frostbite©, HoneyCrisp©, SnowSweet©, and Haralson©) designed for an upper Midwest (zone 3a) environment. After the tree planting project, a survey was administered that examined perceptions of volunteering in community service programs and how connected individuals felt to their community after participation. A Pearson correlation coefficient test identified a highly significant correlation ( r =.934; p <.001) between the variables of community service work as important activities for all persons with feeling better connected to the community. Suggestions for future research involving community service activities within correctional facilities are offered.